2006
DOI: 10.1111/j.1600-0838.2006.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness profile of elite athletes with intellectual disability

Abstract: It can be concluded that high-performance athletes with ID reach physical fitness levels that are equal to or lower than those of able-bodied sportive counterparts. Further research should investigate the importance of reduced muscle strength to be the limiting factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 25 publications
4
32
2
Order By: Relevance
“…Only one study has investigated postural balance and muscle performance among very physically active individuals with ID (van de Vliet, Rintala, Fröjd, Verellen, van Houtte, Daly,Vanlandewijck, 2006). This study examined 313 athletes aged 17 to 49 competing in the International Sports Federation for Para-athletes with an Intellectual Disability's (INAS-FID) Global Games in 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study has investigated postural balance and muscle performance among very physically active individuals with ID (van de Vliet, Rintala, Fröjd, Verellen, van Houtte, Daly,Vanlandewijck, 2006). This study examined 313 athletes aged 17 to 49 competing in the International Sports Federation for Para-athletes with an Intellectual Disability's (INAS-FID) Global Games in 2004.…”
Section: Introductionmentioning
confidence: 99%
“…For motor and skills component, Van de Vliet, Rintala, Fröjd, Verellen, Van Houtte, Daly, & Vanlandewijck (2006) concluded that high-performance II-athletes reached physical fitness levels equal or lower than those of able-bodied sportive counterparts. However, in the present study, coaches and referees indicated that II influenced negatively on several fitness components.…”
Section: Discussionmentioning
confidence: 99%
“…In the side of fitness, several studies reported poor levels on general standard fitness tests in individuals with II (Carmeli et al, 2008;Cuesta-Vargas, Paz-Lourido, & Rodriguez, 2011;Frey, Stanish, & Temple, 2008;Graham & Reid, 2000;Van de Vliet et al, 2006). Cardiovascular fitness was reported by Pitetti, Yarmer, & Fernhall (2001) to be lower in 20m shuttle run test comparing with matched AB-individuals.…”
Section: Influence Of II On Motor Skills and Fitnessmentioning
confidence: 94%
“…They suggested that these differences were related to a central nervous system failure to activate motor units and to some abnormal intrinsic muscle properties. These lower results could be also attributed to other factors including (a) sedentary lifestyle, (b) poor motivation to perform a test (c) the lack of possibilities to take part into physical activities (d) difficulties to accurate fitness assessment in this population, (e) physical characteristics such as short stature, postural control problems, and cardiovascular insufficiency (f) chronotropic incompetence (misbalance between maximal heart rate and metabolic levels at maximal or submaximal effort) and (g) reduced strength (Borji et al, 2014;Graham & Reid, 2000;Stanišić, 2012;Van de Vliet et al, 2006). Several studies indicated that athletes with higher degree of II scored lower in motor skills and fitness tasks (Elmahgoub, Van de Velde, Peersman, Cambier, & Calders, 2012;Golubovic et al, 2012;Lejčarová, 2009).…”
Section: Influence Of II On Motor Skills and Fitnessmentioning
confidence: 99%
See 1 more Smart Citation